Non-publication of Constitutional Tribunal judgments and its consequences (Finding a way out of Poland's rule-of-law crisis: Possible courses of action and reform, 2026)
Chapter Four discusses the issue of the government ceasing to publish the rulings of the Constitutional Tribunal in the Journal of Laws since March 2024, which the author of the report considers a direct violation of the Polish Constitution. These actions, motivated by resolutions of the Sejm and the Council of Ministers, lead to legal chaos and deprive citizens of certainty regarding the legal effects of the issued rulings. The greatest threat is the inability to reopen civil, criminal, and administrative proceedings based on provisions overturned by the Tribunal.As part of corrective measures, the author demands the immediate publication of all overdue rulings and that those responsible for the failure to publish be held constitutionally and criminally liable. He also advocates for the enactment of regulations suspending the time limits for reopening cases and the statute of limitations for damage claims for the duration of the publication freeze. This will ensure that citizens do not lose their rights to seek redress for their grievances due to delays caused by state organs.In the long term, it is proposed to strip the Government Legislation Center of its monopoly on publishing rulings and transfer this competence directly to the Constitutional Tribunal to prevent the government from using obstruction. In the event that conditions for amending the Polish Constitution arise, the author also considers the complete elimination of the Constitutional Tribunal and the transfer of its competencies to a newly created chamber of the Supreme Court.